2019
DOI: 10.3390/cancers11111722
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of an Immune-Related Prognostic Model Based on TP53 Status in Colorectal Cancer

Abstract: Growing evidence has indicated that prognostic biomarkers have a pivotal role in tumor and immunity biological processes. TP53 mutation can cause a range of changes in immune response, progression, and prognosis of colorectal cancer (CRC). Thus, we aim to build an immunoscore prognostic model that may enhance the prognosis of CRC from an immunological perspective. We estimated the proportion of immune cells in the GSE39582 public dataset using the CIBERSORT (Cell type identification by estimating relative subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Subsequently, the risk signature using three genes (GF2BP1 + IGF2BP2 + METTL3) was shown to be an independent prognostic marker of NPC. Accumulating studies showed that the tumor immune microenvironment plays a vital role in the progression and prognosis of various cancers (35). NPC is characterized as a highly immunogenic tumor characterized by high rates of tumorinfiltrating lymphocytes (TILs) (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the risk signature using three genes (GF2BP1 + IGF2BP2 + METTL3) was shown to be an independent prognostic marker of NPC. Accumulating studies showed that the tumor immune microenvironment plays a vital role in the progression and prognosis of various cancers (35). NPC is characterized as a highly immunogenic tumor characterized by high rates of tumorinfiltrating lymphocytes (TILs) (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…FASLG (Fas ligand), a core gene involved in lymphocyte apoptosis and Tcell development, was down-regulated, which meant partial loss of self-regulation in tumor immunity. In recent years, various immunoscore models, based on TILs' proportion, ratio of immune cells, and expression of prognostic genes, have been developed and verified to assess prognosis (51)(52)(53). Though current studies showed relatively good probability of prognostic assessment in part, they focus on the overall distribution of immune cells and total gene expression difference between samples.…”
Section: Discussionmentioning
confidence: 99%
“…The cBio Cancer Genomics database (https://www.cbioportal.org/) was used to investigate the genetic alteration information of 13 m 6 A methylation regulators [20]. Univariate Cox regression analysis was performed to exp lore the relationships between the expression of m 6 A RNA methylation regulators and patients' survival [21]. Then, these 13 m 6 A methylation regulators were entered into a LASSO regression analysis [15].…”
Section: Construction Of Prognostic Gene Signaturementioning
confidence: 99%